Comparative performance of different lines of New Hampshire breed of poultry in Nepal - Adhikari, Dipak; Paudel, Sagar; Baskota, Niraj; Shrestha, Snehi; Chapagain, Purna Bhadra; Poudel, Nabaraj (Nepal Agriculture Research Journal, 2023)
A study was conducted to evaluate the comparative performance of four different lines of New Hampshire (NH) poultry breed collected from different governmental farms of Pokhara, Parwanipur, Khajura and Khumaltar, Nepal. The study was undertaken for seven months from March to September 2020. The study included 160 chicks with 20 male and 20 female from each line. The experiment was conducted in a Completely Randomized Design with four treatments of different lines and eight replications. The results showed that the highest average weight of day-old chicks was found for Khumaltar line and the lowest for Pokhara line (p<0.001). Similarly, the highest fourth week’s weight was found 237.50±16.88 g in Khajura line and the lowest 191.60±26.53 g in Parwanipur line. In case of eight weeks weight, both male and female was the highest in Khajura line, which were 0.72±0.12 kg and 0.52±0.07 kg, respectively. At that stage, the male weight was significant (p<0.001) but non-significant (p>0.05) in female. Similar pattern was found in twelve and sixteen weeks, but the weight of both sex was significant (p<0.001) at twenty and twenty-four weeks. At the final measurement in 24 weeks, the male and female weight was the highest in Khajura line and the lowest in Parwanipur line. The weight of both sexes of Pokhara and Khumaltar lines were similar. Khajura line was better than other lines indicating that this line is more appropriate be used for further improvement of the NH lines of the country.